2,3-Diarylxanthones as strong scavengers of reactive oxygen and nitrogen species: a structure–activity relationship study - Santos, Clementina M.M. (2011)
Xanthones are a class of oxygen-containing heterocyclic compounds widely distributed in nature. The natural derivatives can present different substitutions in the xanthone core that include hydroxyl, methoxyl, prenyl and glycosyl groups. The inclusion of aryl groups has only been reported for a few synthetic derivatives, the 2,3-diaryl moiety being recently introduced by our group. Xanthones are endowed with a broad spectrum of biological activities, many of them related to their antioxidant ability, including the scavenging of reactive oxygen species (ROS) and reactive nitrogen species (RNS), as well as metal chelating effects. Considering the interesting and promising antioxidant activities present in compounds derived from the xanthone core, the main goal of this work was to evaluate the scavenging activity of the new 2,3-diarylxanthones for ROS, including superoxide radical (O2 ), hydrogen peroxide (H2O2), singlet oxygen (1O2), peroxyl radical (ROO ) and hypochlorous acid (HOCl), and RNS, including nitric oxide ( NO) and peroxynitrite anion (ONOO ). The obtained results revealed that the tested 2,3-diarylxanthones are endowed with outstanding ROS and RNS scavenging properties, considering the nanomolar to micromolar range of the IC50 values found. The xanthones with two catechol rings were the most potent scavengers of all tested ROS and RNS. In conclusion, the new 2,3-diarylxanthones are promising molecules to be used for their potential antioxidant properties.